Construction of gene expression vector of yeast SAMDC and tomato transformation mediated by Agrobacterium tumefaciens - DING Shu-li; LI Jian-yong; ZOU Yi-jing; LU Gang; CAO Jia-shu (浙江大学学报. 农业与生命科学版)
S-adenosylmethionine decarboxylase (SAMDC) is a key enzyme involved in the biosynthesis of the polyamines, viz. spermidine and spermine. Two pairs of primers were designed based on the published sequences in the GenBank. The SAMDC gene and E8 promoter were amplified using yeast and tomato genome DNA as templates, respectively. Then two SAMDC gene expression vectors containing CaMV35S and E8 promoters separately were constructed. The SAMDC gene was introduced into tomato genome by Agrobacterium tumefaciens mediated transformation. The PCR and X-Gluc histochemical assay results showed that SAMDC had been integrated into the genome of tomato successfully. The results provided a helpful tool for understanding the physiological function of polyamines and the effects of SAMDC gene on resistance to abiotic stress and fruit color in tomato.